2006
DOI: 10.1073/pnas.0605067103
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and electronic structure studies of aromatic electrophilic attack and hydrogen-atom abstraction by non-heme iron enzymes

Abstract: (4-Hydroxy)mandelate synthase (HmaS) and (4-hydroxyphenyl)pyruvate dioxygenase (HPPD) are two ␣-keto acid dependent mononuclear non-heme iron enzymes that use the same substrate, (4-hydroxyphenyl)pyruvate, but exhibit two different general reactivities. HmaS performs hydrogen-atom abstraction to yield benzylic hydroxylated product (S)-(4-hydroxy)mandelate, whereas HPPD utilizes an electrophilic attack mechanism that results in aromatic hydroxylated product homogentisate. These enzymes provide a unique opportun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
242
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 151 publications
(258 citation statements)
references
References 31 publications
15
242
1
Order By: Relevance
“…Two different reaction channels were identified for Fe IV =O (S=2) enzyme intermediates in previous studies. 81,85,86 The first also involves the unoccupied β-spin d(xz/ yz) orbitals. 81 This is the case for the catalytic cycle of the non-heme iron enzyme 4-hydroxymandelate synthase (HmaS), which is believed to involve a high-spin Fe IV =O intermediate performing an H-atom abstraction reaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two different reaction channels were identified for Fe IV =O (S=2) enzyme intermediates in previous studies. 81,85,86 The first also involves the unoccupied β-spin d(xz/ yz) orbitals. 81 This is the case for the catalytic cycle of the non-heme iron enzyme 4-hydroxymandelate synthase (HmaS), which is believed to involve a high-spin Fe IV =O intermediate performing an H-atom abstraction reaction.…”
Section: Discussionmentioning
confidence: 99%
“…81, 88 Thus, in addition to the more horizontal approach and interaction with the β-spin d(xz/yz) orbitals as in S=1 complexes and geometrically constrained S=2 systems, 81,85 a vertical orientation of the substrate and interaction with the α-spin Fe-O σ* d(z 2 ) orbital, i.e. a σ-FMO mode, is possible for the electrophilic attack by Fe IV =O (S=2) species in enzymatic cycles, as calculated for the non-heme iron enzyme 4-hydroxyphenylpyruvate dioxygenase (HPDD) 81 and for an unconstrained substrate. 86 Thus, in the determination of σ-vs. π-reaction pathways of the Fe IV =O (S=2) species in different enzymatic cycles an investigation of the restrictions imposed by the protein pocket is required.…”
Section: Discussionmentioning
confidence: 99%
“…7,8,14 The structure of the HMS-Co(II)-HMA complex shows that HMA is bound to the metal Figure 2: Active sites in X-ray crystal structures of Amycolatopsis orientalis HMS-Co(II)-HMA and Pseudomonas fluorescens HPPD-Fe(II)-acetate complexes (PDB codes: 2R5V and 1CJX, respectively). Residue names in red for the first shell metal ligands; residue names in blue for the amino acids hydrogen bonding to the first shell metal ligands; ovals mark residues substituted in the mutagenetic studies; hydrophobic residues in green.…”
Section: Hmsmentioning
confidence: 99%
“…15 In the resting form of HPPD the active site iron is six-fold coordinated (2-His-1Glu facial triad and three water molecules) as revealed by X-ray crystal structures (PDB:1SP8,1SP9) and spectroscopic studies. 14,18,19 Results of steady-state kinetics measurements indicated that HPP binds to Fe(II) prior to dioxygen, while CO 2 is the first product released from the active site, similarly to other α-keto acid dependent enzymes. [20][21][22] Respail and co-workers performed QM/MM calculations to test the possible binding modes of HPP in the HPPD active site.…”
Section: Hmsmentioning
confidence: 99%
See 1 more Smart Citation